Incidence and Patterns of Interstitial Lung Disease and Their Clinical Impact on Mortality in Patients with Antineutrophil Cytoplasmic Antibody-Associated Vasculitis: Korean Single-Centre Observational Study - Jang Woo Ha; Jung Yoon Pyo; Sung Soo Ahn; Jason Jungsik Song; Yong-Beom Park; Sang-Won Lee (Journal of Immunology Research)
Objectives. This study investigated the frequency and patterns of interstitial lung disease (ILD) and their clinical effect on all-cause mortality during the follow-up period in patients with antineutrophil cytoplasmic antibody- (ANCA-) associated vasculitis (AAV) in Korea. Methods. The medical records of 255 AAV patients with ILD were retrospectively reviewed. ILD and its patterns, the usual interstitial pneumonia (UIP) and non-UIP patterns, were confirmed using high-resolution computed tomography both at AAV diagnosis and during follow-up. Forced vital capacity (FVC) and diffusing capacity of the lung for carbon monoxide (DLCO) were also obtained. Results. The median age was 65.0 years, and 34.9% were male. ILD occurred in 53 patients, among whom 49.1% developed ILD after AAV diagnosis. Among AAV subtypes, the frequencies of ILD were significantly higher in both patients with microscopic polyangiitis (MPA) and those with AAV having myeloperoxidase (MPO)-ANCA (or P-ANCA) compared to other subtypes. However, there was no statistical significance in AAV subtypes or FVC/DLCO ratio between patients with the UIP and non-UIP patterns. In particular, the cumulative patients’ survival rate was lower in patients with AAV and ILD than in those without ILD. Conclusions. ILD occurred in one-fifth of Korean patients with AAV in this study and was associated with MPA and MPO-ANCA (or P-ANCA). In addition, ILD significantly increased the rate of all-cause mortality in these patients with AAV. Therefore, we suggest the need for more attention and more frequent regular visit for patients with AAV and ILD regardless of the time of ILD occurrence.